Comparative analytical study between parent and daughter hydated cysts fluids isolated from sheep in Iraq - Amal Khalaf; Afrah Maktoof (University of Thi-Qar Journal of Science, 2022)
The importance of the study the chemical composition from trace ele-ments in hydatid cyst fluids was com-ing from the distribution of this infec-tion in Iraq yearly , this is lead to deal with the study of the disease widely . So, the present study was designed to detect some electrolytes in both of par-ent and daughter hydatid cysts by atomic absorption spectroscopy where it is found the presence of ( Pb, P ,Cd ,K ,Na ,Mn ,Cu ,Fe ,Ca ,Mg ,Zn) in both of the parent and daughter hydatid cysts recording Pb (80.93), P(30.17) ,Cd(28.73) ,K(50.23) ,Na(62.88) ,Mn(591.66) ,Cu(405.92) ,Fe (317.42),Ca(200.21) ,Mg(178.32) ,and Zn(151.56) μg\ml in contents of the parent hydatid cyst while the contents of these metals in the daughter hydatid cyst are Pb (61.12), P(22.11) ,Cd(20.82) ,K(36.29) ,Na(54.62) ,Mn(300.22) ,Cu(291.42) ,Fe (101.41),Ca(83.12) ,Mg(98.81) ,and Zn(76.58) μg\ml respectively.